2015
DOI: 10.7603/s40730-015-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

Mini-invasive treatment for delayed or nonunion: the use of percutaneous autologous bone marrow injection

Abstract: Abstract-Delayed union or nonunion of bone fracture is becoming less frequent, but still remains a challenging clinical problem. Autologous cancellous bone grafting that is the gold standard method, often involves donor site morbidities and complications. Once these fractures have been mechanically stabilized, other local factors should be investigated to promote delayed healing. The purpose of this study was to evaluate the initial outcome of the percutaneous injection of autologous bone marrow after concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…15 Hau et al reported a 100% union rate in their study with all 10 patients achieving good bone union at the fracture site. 16 We had a union rate of 93.3% in our study. A review of literature of other studies also showed good union rates following bone marrow infection which compares well with that of our study.…”
Section: Discussionmentioning
confidence: 67%
“…15 Hau et al reported a 100% union rate in their study with all 10 patients achieving good bone union at the fracture site. 16 We had a union rate of 93.3% in our study. A review of literature of other studies also showed good union rates following bone marrow infection which compares well with that of our study.…”
Section: Discussionmentioning
confidence: 67%
“…There was no sign of infection or hematoma growth at the aspiration site. Persistent discomfort has not been reported after iliac crest bone marrow aspiration [26] .…”
Section: Case Illustrations Casementioning
confidence: 96%
“…Year Outcome Sim et al [11] 1992 9/11 (81.8%) Bhargava et al [8] 2007 25/28 (89.3%) Elsattar et al [22] 2014 16/20 (80%) Connolly et al [23] 1991 18/20 (90%) Sahu [24] 2018 82/93 (88%) Singh et al [2] 2013 10/12 (83.3%) Thua et al [25] 2015 10/10 (100%) Hernigou et al [14] 2006 88.3% Sugaya et al [26] 2014 76% Present study 2023 28/30 (93.3%)…”
Section: Authorsmentioning
confidence: 99%